The establishment of farmer groups in increasing agricultural productivity in Ketapang Regency - Novira Kusrini; Hastiadi Hasan; Rudi Alfian; Maswadi (Tanjungpura International Journal on Dynamics Economics, Social Sciences and Agribusiness, 2023)
: In order to promote farming operations and enhance the welfare of the farmers themselves, there is an urgent and essential requirement for farmers to strengthen farmer group structures. However, most farmers still don't understand the importance of farmer groups, particularly in Ketapang Regency. Therefore, the goal of this research is to determine how farmers perceive the role that farmer groups have played thus far, as well as what institutional issues are preventing and encouraging an increase in agricultural production. In order to determine the best course of action for raising agricultural output in Ketapang Regency. The research is conducted in 6 sub-districts in Ketapang Regency. While the respondents were food crop and vegetable farmers come to 60 people. The method of taking respondents is by purposive sampling. The results of the study show that the institutional role of production facilities, agricultural machinery, capital and marketing has not run optimally. It is necessary to strengthen institutions so that it is expected to increase farmers' access to these institutions. Acceleration of borrowing agricultural tools and sharing information is a priority effort to do because it has an impact on increasing agricultural productivity in Ketapang Regency.